Indigenous Efflorescence and Tjåenieh in Southern Saepmie. Rethinking Language Revitalization Research in Conversation with a Saemie Illustrator - Gjelde-Bennett, Kaja Nan (UiT Norges arktiske universitet, 2020)
Proclaiming an international Indigenous societal revolution is taking place, anthropologist and language revitalization researcher, Gerald Roche develops the concept of Indigenous efflorescence to identify and investigate sites of Indigenous language and cultural flourishing in spite of colonialism. Conversely, the South Saemie language has been framed as “severely endangered” and the community a struggling “minority within a minority” within the larger Saemie context as an Indigenous people in Scandinavia and Russia. This master’s thesis aims to explore first, how may this relatively new theoretical concept of Indigenous efflorescence be directly applied to a particular Indigenous language context, in this case the South Saemie language community? Additionally, what can Indigenous efflorescence as a practical analytical tool contribute to Indigenous language research? To gather empirical data within an Indigenous research paradigm, I employ Indigenous methodologies and methods, principally the conversational method described by Cree scholar Margaret Kovach, to develop a collaborative working relationship with self-identifying South Saemie Illustrator, Katarina Blind. I then utilize Indigenous efflorescence as a theoretical framework to perform a close analysis of two illustrations pertaining to the South Saemie language situation from Katarina Blind’s Instagram page, Tjåenieh. Framing Katarina Blind’s work as a practice of Indigenous efflorescence, Katarina’s illustrations paired with her own voice highlight an individual’s experience within the contemporary South Saemie language community in how Katarina does Indigenous efflorescence and how she feels about the current situation. Finally, the research project discusses the outcomes of an individual focused, micro-level approach to understanding the South Saemie language context through practices of Indigenous efflorescence, and then more generally what an Indigenous efflorescence perspective can contribute to Indigenous language research.